The music in the literacy process from the perspective of neuroscience: contributions from PIBID-Pedagogy - Vieira, Débora (2022)
This text presents an experience of undergraduate students in Pedagogy at the University of the State of Minas Gerais - UEMG, Divinópolis-MG, scholarship holders of the Institutional Scholarship Program for Teaching Initiation - PIBID between 2020 and 2021. Faced with the difficulties and challenges presented in the unusual pandemic scenario, the strategy chosen by the undergraduates was to insert music into literacy-oriented activities because of its ability to stimulate multiple regions of the brain. The objective of this text is to present how literacy can be effective and attractive to children, through the training of teachers in neuroscience studies, on the action of music on the brain. The work of the fellows was carried out remotely due to the requirement of social isolation, the activities for the children were printed and delivered at the Antonieta Fonseca Municipal School to their responsible fortnightly, in addition to keeping in touch with students via social network on the internet. The set of activities developed showed a lot of interaction among children, teachers and family members and culminated in the First Exhibition of PIBID-Pedagogy of UEMG - Divinópolis. The work instigates further investigations on the insertion of music in the literacy process from the neuroscience perspective.